Pojęcie nieruchomości ziemskiej na gruncie dekretu o przeprowadzeniu reformy rolnej - Fruba, Szymon (Kwartalnik Prawa Publicznego, 2012)
This analysis is devoted to a certain issue connected with a decree on a land reform. There was a land reform after the second word. The State Treasury acquired some categories of land properties. Subsequently the lands were given to enlarge other agricultural farms or creation new ones. Previous owners were given nothing instead. Transformation and restitution in Poland let the previous owners or their legal successors taking successful legal actions. It is often justified that the land do belong to the category of land property. However, a meaning of a notion: land property was replaced by a notion agricultural property, there two notions should not be identified. Taking into account provisions of the decree on a land reform it should be concluded that a scope of the meaning of the notion: land property is wider than the meaning of the notion: agricultural land property. It also should be stated that the meaning of the notion of agricultural land property is wider than the meaning of a notion of term: agricultural arable land. According to a decree on a land reform on the purposes of the agricultural reform not only were destinated agricultural land properties but also other nonagricultural land properties. Through an amendment to a decree on a land reform on the 19th of January 1945 there were extended the purposes which the agricultural reform should obtain and enlenghten also the category of land. Thus, the meaning of the notion land property includes agricultural land property and also non – agricultural land properties, especially non-arable lands located outside the borders of towns. Outside the legal scope of notion: land property there are excluded municipal properties (not connected with agriculture). Because of the fact that in those days lands located outside towns were exploited nearly totally agriculturally.